'Black curtain, Brown window' - A case of recurrent intermittent idiopathic Brown syndrome with atypical presenting symptoms - Voichanski Shilo; Rabinovich Ronen; Rappoport Daniel (American Journal of Ophthalmology Case Reports, 2022)
Brown syndrome is characterized by limited elevation of the eye in an adducted position, most often secondary to mechanical restriction of the superior oblique tendon/trochlea complex. It can be constant or intermittent/recurrent.We report on a 5 years-old boy who complained of seeing dark curtain and had strange head movements. He had similar symptoms 6 months prior. Examination revealed binocular vertical diplopia, multiplanar abnormal head position and limitation of the elevation of the right eye adduction only. Pain was elicited during attempt to elevate and adduct the right eye, with downshoot of right eye, and reflexive eyelid closure.The patient was diagnosed with intermittent idiopathic Brown syndrome.One day later, the patient was found to be asymptomatic, and had spontaneous resolution without any treatment.Literature on acquired Brown's syndrome in children is scarce.Very few have described the idiopathic intermittent or recurrent form. The acute, short and recurrent pattern of our patient's symptoms showed an atypical, non-classical presentation and course. The initial misleading symptoms presented a diagnostic challenge. These might be explained by the prominent acute inflammatory component upon presentation, and we suggest two theories that might explain such an atypical clinical course.